(untitled) (International Journal of Latest Technology in Engineering Management & Applied Science, 2026)
School conflict management is often judged by whether it restores visible order. In boarding Senior High Schools, however, students and staff continue to live and work together after disputes have been formally resolved; therefore, effectiveness also depends on whether disciplinary processes are perceived as fair, respectful and legitimate. This article examines how heads, senior house staff, guidance and counselling coordinators and student leaders perceived the effectiveness of conflict-management strategies in two public boarding Senior High Schools in the Tarkwa-Nsuaem Municipality of Ghana. Drawing on a qualitative multiple-case study involving 24 participants, the article argues that effectiveness was interpreted through two related but distinct lenses: compliance-based effectiveness and legitimacy-based effectiveness. School A associated effectiveness mainly with discipline, deterrence, improved attendance and behavioural compliance, while School B associated it more strongly with engagement, relational repair, calm and follow-up. Across both cases, strategies were judged more positively when they involved timely response, meaningful voice, consistency, reason-giving, counselling support and fair stakeholder involvement. Negative cases showed that perceived bias, failure to hear parties, external reversal of decisions and weak consultation could undermine confidence even where formal disciplinary structures existed. The article contributes to school leadership literature by showing that conflict-management effectiveness in boarding Senior High Schools should be assessed not only by reduced misconduct but also by the fairness of the process through which order is achieved.